Recollecting a lost dialogue: Structural Realism meets neoclassical realism. (September 2019) - Smith, Keith
Since its appellation, much work has sought to consolidate neoclassical realism. Specifically, a number of variations on the neoclassical theme have reconceptualised the third-image and carved out a distinctly European neoclassical variant. This article contributes by recollecting the Structural Realism of Logic of Anarchy . In unpacking Structural Realism's framework and dissecting its engagement with inter alia Kenneth Waltz, this article illustrates the importance of Logic 's conceptualisation of the system, particularly in terms of anarchy's logic. This framework can enrich a number of debates within the neoclassical realist community, especially concerning third-image change and the possibility of a neoclassical realism in and of Europe, while also contributing to debates regarding the strategic actor-ness of the European Union. While Logic and its framework might appear dated, the article submits that one of its principal motifs, anarchy, along with realism's normative ethos may remind us of International Relation's (IR's) healthy pluralism.